PENGARUH KOMPRES HANGAT DALAM MENURUKAN INTENSITAS NYERI PADA PERSALINAN KALA I FASE AKTIF DI KLINIK PRATAMA NIAR PATUMBAK - Nani Zulfikar (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2025)
Pain during labor is common and experienced by almost 90% of mothers. It can be traumatic, causing some mothers to fear pregnancy and childbirth again, fearing the same experience. Applying warm compresses can be an efficient way to help mothers relieve pain and provide comfort during labor. This study aimed to assess the effect of warm compresses on pain levels in the active phase of first stage labor. This study was a quantitative pre-experimental study with a one-group pretest-posttest design using purposive sampling. Thirty-eight mothers giving birth at Klinik Pratama Niar Patumbak were sampled. Data were collected using an assessment sheet and analyzed using a paired t-test with a p value of > 0.05.